The Effect of Cytokinin Spraying and Harvest Cutting on Essential Oil Production and Growth Characteristics of Thyme (Thymus vulgaris L.) - Y Norouzi; M Ghobadi; M Saeidi; D Kahrizi; H Dogan (پژوهشهای زراعی ایران)
IntroductionThyme (Thymus vulgaris L.) is a perennial plant that belongs to Lamiaceae family, and native to the Mediterranean regions. Thyme is used in the medical, cosmetic and food industries due to its unique aroma and taste. The yield of thyme can be affected by environmental factors and agricultural management. Harvest cutting is one of the important factors determining the quantitative and qualitative characteristics of the thyme. It has also been reported that exogenous application of plant growth regulators at low concentrations has led to yield improvement. Cytokinins (CKs) are one of the five main types of plant growth regulators (PGRs) that affect plant growth and development. In addition to enhancing cell division and growth, CKs also prevent plant aging by inhibiting the breakdown of chlorophyll, nucleic acids, proteins, and other substances. CKs play a role in the transport and accumulation of photosynthesis products and affect the activity of enzymes. CKs also stimulate the growth of lateral branches, too. This study was conducted to investigate the effect of foliar spraying of cytokinin (benzylaminopurine) during harvest cuttings on the essential oil production and growth of thyme plant.Materials and MethodsThis experiment was carried out at the research farm of Razi University, Kermanshah, Iran (Longitude 47°, 9' east and latitude 34°, 21' north, 1319 m above sea level) during three consecutive years of 2017, 2018 and 2019. The research was conducted as a factorial experiment based on a randomized complete blocks design with three replications. The first factor was the harvest cutting (late June and late September) and the second factor was the concentrations of cytokinin (0, 100, 200 and 400 μM BAP). The measured traits included plant height, stem diameter, number of branches, leaf, stem and total dry weight, percentage and yield of essential oil. The analysis of variances (ANOVA) of data was performed using SAS ver.9 software and the means comparison was done using LSD test at 5% probability level.Results and DiscussionThe results of analysis of variance showed that the effect of harvest cutting on the traits of plant height, stem diameter, number of branches, leaf, stem and total dry weights and essential oil yield was significant, but its effect on the essential oil percentage was not significant. Also, the effect of foliar spraying of BAP was significant on all the mentioned traits. The interaction effect of harvest cutting × BAP spraying was significant on the number of branches, dry weight of leaves and stems, total dry weight and essential oil yield. A comparison of means showed that the highest plant height, number of sub-branches, leaf dry weight, stem dry weight and total dry weight (4355 kg ha-1) were obtained by foliar spraying of 400 µM BAP. The percentage of essential oil increased with the increase of BAP concentration. The highest essential oil (2.35%) was obtained by foliar spraying of 200 μM BAP. The highest and lowest essential oil percentage were obtained in 2020 and 2018 experiments, respectively. Also, the yields of essential oil were different in different cuttings under the influence of BAP foliar application. The increasing of the essential oil yield in the first harvest was higher compared to the second harvest. Foliar spraying of 400 μM BAP in the first harvest produced the highest essential oil yield (59.95 kg ha-1).ConclusionIn general, the results of this study indicated that cytokinin spraying during the first harvest significantly influenced on the enhancement of traits such as plant height (16%), number of lateral branches (59%), leaf dry weight (200%), total dry weight (194%), and essential oil production (108-217%) in thyme. Additionally, as the plant aged (in the third year of the experiment), this enhancement in essential oil production was more. To enhance essential oil yield and vegetative growth of thyme, it is recommended to apply 400 µM cytokinin spraying during the first harvest.